2010
DOI: 10.3233/jad-2010-101182
|View full text |Cite
|
Sign up to set email alerts
|

Does the Combination of the MMSE and Clock Drawing Test (Mini-Clock) Improve the Detection of Mild Alzheimer's Disease and Mild Cognitive Impairment?

Abstract: There is currently a need to develop tools to identify patients with mild AD and mild cognitive impairment (MCI). We determined the validity and reliability of a brief, easily administered cognitive screening battery consisting of fusion of two well-known brief tests (Mini-Mental Status Examination [MMSE] and Clock Drawing Test [CDT]) (Mini-clock) to differentiate between patients with mild AD, MCI, and healthy control subjects. 66 consecutive patients with mild AD, 21 with MCI, and 66 healthy controls seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 29 publications
4
37
1
5
Order By: Relevance
“…However, such a comprehensive evaluation of cognitive state is available only to a small proportion of the patients in need, since such evaluations are provided mostly at specialized memory clinics. Therefore, determining an accurate screening method for MCI, which could serve as a preselection of the persons at higher risk, has been the subject of many research studies in the past decade (Cacho et al, 2010;Ehreke, Luppa, König, & RiedelHeller, 2010;Ladeira, Diniz, Nunes, & Forlenza, 2009;Nasreddine et al, 2005;Nishiwaki et al, 2004;Peters, 2009). There is no consensus regarding which test should be used, but several candidate instruments are available.…”
mentioning
confidence: 98%
“…However, such a comprehensive evaluation of cognitive state is available only to a small proportion of the patients in need, since such evaluations are provided mostly at specialized memory clinics. Therefore, determining an accurate screening method for MCI, which could serve as a preselection of the persons at higher risk, has been the subject of many research studies in the past decade (Cacho et al, 2010;Ehreke, Luppa, König, & RiedelHeller, 2010;Ladeira, Diniz, Nunes, & Forlenza, 2009;Nasreddine et al, 2005;Nishiwaki et al, 2004;Peters, 2009). There is no consensus regarding which test should be used, but several candidate instruments are available.…”
mentioning
confidence: 98%
“…MMSE asks questions that assess 5 areas of cognitive functioning (i.e., orientation, immediate memory, attention/concentration, delayed recall, language) (Shigemori, Ohgi, Okuyama, Shimura, & Schneider, 2010). The results of a few surveys indicate that the MSSE has become the most commonly used cognitive test by the health professionals such that approximately 9 out of 10 experts have reported using the test predominantly (Cacho et al, 2010). Farmer and his colleagues (1995) showed that in elderly people with baseline MMSE>23, education was a significant predictor of cognitive decline, not only in the elderly but also in younger participants.…”
Section: Introductionmentioning
confidence: 99%
“…MMSE is a commonly used screening tool for cognitive impairment in older adults. The test can be used to distinguish between older adults with and without neuropsychiatric disorders and as a follow up test to measure the progress of the disorder across time (Cacho et al, 2010). MMSE asks questions that assess 5 areas of cognitive functioning (i.e., orientation, immediate memory, attention/concentration, delayed recall, language) (Shigemori, Ohgi, Okuyama, Shimura, & Schneider, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The CDT has shown good sensitivity in discriminating mild cognitive impairment (sensitivity = 0.76; Cacho et al 2010) and Alzheimer's disease (sensitivity=0.81; Schramm et al 2002).…”
Section: Methodsmentioning
confidence: 98%